Eudraces barclayi sp. nov., with some notes on the genus Eudraces Marshall (Coleoptera: Curculionidae: Entiminae: Myorhinini) - Borovec, Roman; Nakládal, Oto (Zootaxa, 2018)
Eudraces barclayi sp. n. is described from South Africa, illustrated and compared with other species of the genus. Echinocnemodes Voss, 1962 is proposed as a new junior synonym of Eudraces Marshall, 1926. Holcolaccus sparsus (Voss, 1959) is proposed as a new combination from Eudraces Marshall, 1926. Eudraces zumpti Voss, 1959 is a new junior synonym of Eremnus angustirostris Marshall, 1937. A lectotype is designated for Eudraces flavirostris Marshall, 1926. A key to the known Eudraces species is given.